ANALISIS DAMPAK LINGKUNGAN (AMDAL) TEMPAT PEMBUANGAN AKHIR (TPA) IWAKA KABUPATEN MIMIKA - Eka Wahyu Fandi; Anita Zilvana; Nova Linda (CV. Adiba Aisha Amira, 2026)
Final Disposal Sites (TPA) play a strategic role in the regional waste management system, but they also have the potential to cause significant environmental impacts if not managed properly and sustainably. This study aims to analyze the environmental impacts of the presence of a final disposal site (TPA) in Mimika Regency by examining the physical, biological, and socioeconomic aspects of the surrounding community. The study employed a qualitative-descriptive approach through documentation studies, field observations, and analysis of relevant Environmental Impact Assessment (EIA) documents. The analysis indicates that landfill activities have the potential to cause negative impacts in the form of groundwater pollution due to leachate, air pollution due to methane gas and unpleasant odors, and a decline in soil quality around the disposal site. Furthermore, socioeconomic impacts were identified, such as public health problems, reduced environmental comfort, and changes in the livelihoods of local residents. However, the presence of the TPA also has a positive impact in the form of employment opportunities for scavengers and waste managers. Therefore, more optimal environmental management efforts, the implementation of sanitary landfill technology, and ongoing monitoring are needed to minimize negative impacts and maintain environmental sustainability in Mimika Regency